The Mediating effect of Conflict Management styles of School Heads on the relationship between Ethical Climate and Organizational Commitment among Public Elementary Schools in region XI - Bernaldez, ElizabethA; Gempes, Gloria P (International Journal of Management Excellence (ISSN: 2292-1648), 2016)
This study aimed to investigate the mediating effect of conflict management styles of school heads on the relationship between ethical climate and organizational commitment of teachers among 520 teachers in Davao Region, Philippines. This study employed non-experimental design utilizing descriptive correlation technique. The statistical tools used were mean, pearson-r and regression technique. Research instruments on conflict management styles, ethical climate and organizational commitment which were pilot tested and content validated were used as sources of data. Using pearson-r, the results revealed significant relationships between ethical climate, organizational commitment of teachers, and conflict management styles of school heads. Utilizing medgraph Sobel z-test, the results of the study revealed partial mediating effect of conflict management styles of school heads on the relationship between ethical climate and organizational commitment of teachers. This implies that the mediating role played by conflict management styles of school heads partially assisted in clarifying the process that was responsible for the relationship between ethical climate and organizational commitment of teachers.